Space and Interracial Marriage: How Does the Racial Distribution of a Local Marriage Market Change the Analysis of Interracial Marriage in Brazil? - Maria Carolina Tomás (Revista Latinoamericana de Población)
This article focuses on the following question: How would interracial marriage rates change when considering the racial distribution of the local marriage market? I used data from the Brazilian Census for the years 1991 and 2000 and loglinear models. The results show that homogamy-heterogamy rates have traditionally been overestimated, as demonstrated by a change that ranges between 15.3 percent and 43.2 percent, when the local racial distribution of spouses is considered. The gap between the percentage differences is smaller in 2000 than in 1991. When analyzing the homogamy-heterogamy rates for each marriage market, one observes that the interaction between a spouse’s race and the marriage market is important, with very few exceptions. In addition, although most meso-regions have homogamy-heterogamy rates similar to the average, there are some important regional differences, especially in the South, where the levels are higher than the average.